2016
DOI: 10.1118/1.4962475
|View full text |Cite
|
Sign up to set email alerts
|

Assessing task performance in FFDM, DBT, and synthetic mammography using uniform and anthropomorphic physical phantoms

Abstract: This study shows that an anthropomorphic phantom and lesions inserts may be used to conduct a reader study. Detectability was significantly lower for synthetic mammography than for FFDM or DBT, for all conditions. Additionally, observer performance was consistently lower for the anthropomorphic phantom, indicating the greater challenge due to anatomical background. Because of this, it may be important to use realistic phantoms in observer studies in order to draw conclusions that are more clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…In addition, just like in a real mammogram, the calcification‐like signal in our phantom might be masked by a dense fibro glandular‐like area. This is in agreement with the study by Ikejimba et al, where signal contrast was found to be dependent on whether the signal was placed in a region of fibroglandular or adipose tissue of their structured phantom …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, just like in a real mammogram, the calcification‐like signal in our phantom might be masked by a dense fibro glandular‐like area. This is in agreement with the study by Ikejimba et al, where signal contrast was found to be dependent on whether the signal was placed in a region of fibroglandular or adipose tissue of their structured phantom …”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the study by Ikejimba et al, where signal contrast was found to be dependent on whether the signal was placed in a region of fibroglandular or adipose tissue of their structured phantom. 27 The strength of this study is the use of a physical anthropomorphic breast phantom that is realistic in terms of structure, and the use of real acquired images with embedded calcification-like discs to assess the quality of image processing. Although limited to calcification detection, a considerable number of parameters were studied, dose, calcificationlike signal size, imaging systems, 'for processing', and 'for presentation' DM images were used.…”
Section: Discussionmentioning
confidence: 99%
“…Although trends were found to be similar, the absolute values of threshold contrasts in homogeneous backgrounds were lower than in structured backgrounds. This finding is in agreement with the study of Ikejimba et al . who evaluated human observer performance in uniform and anthropomorphic backgrounds for several breast imaging modalities and concluded that it is important to use realistic phantoms when assessing the clinical relevance of breast imaging systems.…”
Section: Discussionsupporting
confidence: 92%
“…42,43 Although trends were found to be similar, the absolute values of threshold contrasts in homogeneous backgrounds were lower than in structured backgrounds. This finding is in agreement with the study of Ikejimba et al 44 who evaluated human observer performance in uniform and anthropomorphic backgrounds for several breast imaging modalities and concluded that it is important to use realistic phantoms when assessing the clinical relevance of breast imaging systems. When evaluating the whole imaging chain including image processing or when comparing to the use of other X-ray breast imaging systems, it is, therefore, important to switch toward using realistic anthropomorphic phantoms.…”
Section: Ain1supporting
confidence: 92%
“…The CIRS BR three‐dimensional (3D) phantom (CIRS Inc., Norfolk, VA) is a physical phantom that is not based on patient anatomy, but instead mirrors the power law spectrum properties of the breast. In addition, some virtual phantoms were successfully realized and used in scientific studies, such as the UPENN and Duke physical phantoms. A number of researchers have demonstrated how task‐performance‐based image quality can be assessed using physical phantoms.…”
Section: Introductionmentioning
confidence: 99%